MENGKAJI DAN MENGANALISIS QUANTUM IKHLAS OLEH ERBE SENTANU - Husin Husin (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2018)
Ikhlas becomes a powerful word that is often spoken when someone is no longer able to overcome all the problems of life. In addition, the word Ikhlas can also be the last words used by people who are not persistent in fighting for their destiny. Erbe Sentanu with the theory of Quantum Ikhlas tries to offer an applicable concept of an Ikhlas word that he mixes from various religious teachings, theories and thoughts of religious figures. Erbe Sentanu believes that when humans express everything (good or bad) that has happened, in fact, the person has activated extraordinary energy that can attract and influence positively and can even reverse any deadlock to unexpected solutions. Researchers tried to dissect the contents of Erbe Sentanu's book entitled Quantum Ikhlas The Power of Positive Feeling by using a type of research library research and content analysis. In addition, when analyzing the contents, researchers also tried to approach the Sufism approach so that it could enrich the contents of the book. The conclusions from this study are how to achieve happiness through unusual new intelligence, which is about the ability to rule over yourself and win a war against yourself while achieving ultimate happiness. Keywords: Ikhlas, Brainwave, Positive Thinking, Positive Feeling.